Cyberbullying pada Kolom Komentar Tiktok @Denise_Cariesta dan Implementasinya sebagai Media Pembelajaran - Annissa, Nurul Huda Fitri; Dewi Kusumaningsih; Titik Sudiatmi (GERAM: Gerakan Aktif Menulis, 2022)
This study aimed to describe cyberbullying actions carried out by users in @denisecariesta TikTok's comment column and its implementation as a learning media. This study used a qualitative descriptive research method with data sources in the form of words and sentences in @DeniseCharista TikTok's comment column. Data were collected using documentation, reading, and note-taking techniques, which were then analyzed using the Analysis Interactive Model from Miles and Huberman. The results obtained from this study are many users who abuse one by using the comment column as a booth to carry out cyberbullying, which can harm other parties. The research result reveals that six forms of cyberbullying were found in @denisecariesta TikTok's comment column. Further, TikTok can be an alternative medium for learning literature and language in schools, especially at the senior high school level.